2009
DOI: 10.2215/cjn.04810908
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Biomarkers in the Early Detection of Acute Kidney Injury after Cardiac Surgery

Abstract: Background and objectives: Serum creatinine (Scr) does not allow for early diagnosis of acute kidney injury (AKI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
249
3
20

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 350 publications
(287 citation statements)
references
References 38 publications
10
249
3
20
Order By: Relevance
“…However, if so, patients without AKI who receive furosemide may have a marked diuresis, diluting urinary NGAL, whereas patients with evolving AKI may have a blunted response with less urinary dilution, thus enhancing the apparent discriminant ability of urinary NGAL for AKI. Although adjusting NGAL values for urinary creatinine may have been instructive in this regard, urinary creatinine was not measured, and several previous authors have reported limited incremental benefit in doing so (8,11). Additionally, data on perioperative diuretic administration or urine Figure 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if so, patients without AKI who receive furosemide may have a marked diuresis, diluting urinary NGAL, whereas patients with evolving AKI may have a blunted response with less urinary dilution, thus enhancing the apparent discriminant ability of urinary NGAL for AKI. Although adjusting NGAL values for urinary creatinine may have been instructive in this regard, urinary creatinine was not measured, and several previous authors have reported limited incremental benefit in doing so (8,11). Additionally, data on perioperative diuretic administration or urine Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Five milliliters of urine was collected after induction of general anesthesia and before surgical incision, on completion of cardiopulmonary bypass and again at 3, 18, and 24 hours later. Samples were processed immediately and stored at Ϫ20°C for up to 3 months, a period for which NGAL has been reported to be stable (11). Urinary NGAL level was determined by ELISA assay using a commercially available ELISA kit (Antibodyshop, Gentofte, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…ELISA methods were performed as described previously for NGAL (21), KIM-1 (22), and IL-18 (23), with intra-and interassay variability for all biomarkers documented at Ͻ10%. Standard hospital laboratory systems were used to measure urine sodium and urea.…”
Section: Biomarker Measurementsmentioning
confidence: 99%
“…Underscoring this continuum is a recent article examining NGAL and other urinary biomarkers after cardiac surgery. 3 In that study, regardless of whether the patient was considered to have or have not experienced AKI (using the same definitions used by Siew et al 1 ), a rise from the baseline value with subsequent fall back to baseline was seen over time. Stated another way, even patients without any significant change in creatinine experienced a rise and fall in their urinary NGAL.…”
mentioning
confidence: 93%